Innovative measures for integrating renewable energy in the German medium-voltage grids - Benjamin Bayer; Adela Marian (Energy Reports, 2020)
Grid integration remains one of the key challenges related to the worldwide expansion of distributed renewable energy systems. This paper presents innovative measures for increasing the hosting capacity of distribution grids with a focus on the medium-voltage grid, based on representative interviews with leading large-scale distribution system operators (DSOs) from Germany. For grid optimization, DSOs have implemented dynamic voltage control in substations, adapted the grid structure for renewables, applied the “N minus zero” rule for planning grid operation and used the capability of renewable energy systems to provide reactive power. For grid expansion, DSOs have installed voltage regulators, voltage-regulated distribution transformers, substations used exclusively for renewables, and express feeders that connect substations with the generation centers. This practical experience should also prove relevant for other countries currently planning the expansion of distributed renewable energy systems.